Osobowość organizacji - założenia teoretyczne - Barabasz, Adela (Organizational personality - basic assumptions, 2005)
Some fundamental assumptions concerning the concept of organizational personality are presented in the paper. The author shows that applying our knowledge of the phenomena and mechanisms governing the lives of individuals and groups may be useful in explaining phenomena and mechanisms arising in the realm of the functioning of an organization. She attempts to demonstrate that employing the idea of an organizational personality will not only help in understanding a given organization better, but also in running it more efficiently. The author shows that viewing an organization through the prism of the mechanisms of personality function will allow management to exploit the potential of a given organization more effectively and to cope with crisis situations arising within the organization, such as the broadly construed issue of change, more efficiently.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 106-119